The case of the murdered muckraker - Osler, Rob (Osler, Rob. Harriet Morrow investigates, 2026)
Chicago, 1898. In the midst of the Progressive Era, twenty-one-year-old junior detective Harriet Morrow is determined to prove she's more than a lucky hire as the Prescott Agency's first woman operative. But her latest challenge--a murder case steeped in scandal--could become a deadly setback . . . As the Windy City thaws from a harsh winter, Harriet Morrow finds herself doubting her investigative skills when she's assigned to solve a high-stakes murder case well above her pay grade. And there's also a catch. Harriet must somehow blend in as an "unremarkable" young woman--one who feels confident in skirts, not men's clothing--on a quest to infiltrate the immigrant community at the center of the grisly crime . . . The mystery has more twists and turns than her morning bike commute, with a muckraker found murdered in a southside tenement building after obtaining evidence of a powerful politician's corruption. While Harriet gains the trust of the tenement's women residents to gather clues, the undercover mission reveals an innocent mother might have been framed for the crime--and exposes ties to another violent death . . . Harriet soon realizes she has few allies as new dangers explode around her. Enlisting the help of Matthew McCabe, her only true confidante at the agency, and growing more protective of her budding relationship with the lovely Barbara Wozniak, Harriet will need to survive rising threats to assert her place in a world that's quick to dismiss her--and out a killer who's always one step ahead . . .